ERDOSTEINE: AN EFFECTIVE ANTIOXIDANT FOR PROTECTING COMPLETE FREUND’S ADJUVANT INDUCED ARTHRITIS IN RATS - SYNMON, BANYLLA; ROY, SANHATIDUTTA; MAJEE, SUTAPA BISWAS; PAUL, MEGHNA; DASGUPTA, SANDIPAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of this study was to evaluate the protective effect of Erdosteine on complete freund’s adjuvant (CFA) induced arthritic rats. Methods: Wistar Albino rats of 100–250 g were divided into five groups (n=6) and administered with 0.1 ml of CFA subcutaneously into the left hind paw except the negative control group. The standard group received methotrexate (MTX) 0.075 mg/kg body weight orally. Besides, the test groups received Erdosteine orally at a dose 10 mg/kg and 20 mg/kg bodyweight for 12 days. The changes in body weight, paw volume, hematological parameters, radiographical, and histological findings were the indicators to evaluate the efficacy of the test product. Discussion: Significant change in the body weight, paw volume, radiographical, hematological, and histological parameters were observed which supports the remarkable reduction of the arthritic development in the standard and test groups compared to the untreated group. However, the test group (Erdosteine) with the dose 20 mg/kg shows to be more potent than the test group (Erdosteine) with a dose 10 mg/kg and the standard group (MTX) to reduce the arthritic effect. Results: The test group with 20 mg/kg Erdosteine showed much better outcome than the standard group at significant (p<0.05). Therefore, Erdosteine acting as an anti-inflammatory and anti-oxidant is effective at a dose 20 mg/kg in treating the progression of rheumatoid arthritis in rats.